PENGARUH WAKTU PENYEMPROTAN TERAKHIR SEBELUM PANEN TERHADAP RESIDU PROFENOFOS DAN KARAKTERISTIK SENSORIS KUBIS (Brasicca oleracea var capitata) - Teja Agustina, G. A. M. D.; Lani Triani, I G A; Mulyani, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2016)
This research were aimed to 1) determine the effect of last spraying time before harvest to profenofos residues, 2) to determine the effect of last spraying time before harvest to sensoris characteristic on cabbage and 3) to investigate the correlation between final spraying time with insecticide residue 4) to investigate the correlation between final spraying time with sensoris characteristic on cabbage. This research used randomized block design with single factor. The factor has final spraying time consist of 5 levels namely 0, 2, 4, 6, and 8 days before harvest. This research were gruped into 3 based on harvest time so that resulted into 15 units experiment. The parameter that had been observed were profenofos insecticide residue levels of the cabbage, the characteristic of cabbage and correlation between a final spraying time to profenofos insecticide residue levels and characteristic of cabbage. The result showed that the final spraying time before harvest had effected to profenofos insecticide residues and evaluation sensory on cabbage with treatment 0 ,2, 4, 6, and 8 day before harvest were 0.44 mg/kg, s 0,23 mg/kg, 0.16 mg/kg, 0.14 mg/kg, 0.09 mg/kg, sensory evaluation on characteristics preferred by the value of the color amount of 3.75 (light green to green), texture amount of 3.90 (rather hard until hard) and the value of damage from 1.50 to 4.45. The correlation between final spraying time to profenofos insecticide residue had coefficient correlation at 0.98, for color at 0.93, for texture at 0.91 and for value of damage at 0.97 (strongest). Keywords: Cabage, final spraying time, profenofos and residues
Keywords: 82